Respuesta :

Since this is a right triangle, we can use the Pythagorean Theorem to help us.

 [tex](length-of-leg1)^2+(length-of-leg2)^2 = (length-of-hypotenuse)^2\\[/tex]

Known information:

  • one leg's length: 7 cm
  • hypotenuse's length: 25cm

Now let's plug the known information into the equation:

 [tex]7^2 + (length-of-leg2)^2=25^2\\(length-of-leg2)^2 = 25^2-7^2\\\\(length-of-leg2)^2 = 576\\\\length-of-leg2=24[/tex]

Thus the length of the other leg is 24cm.

Hope it helps!

ACCESS MORE